2009
DOI: 10.1158/1541-7786.mcr-09-0004
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 (COX-2) Negatively Regulates Expression of Epidermal Growth Factor Receptor and Causes Resistance to Gefitinib in COX-2–Overexpressing Cancer Cells

Abstract: Overexpression of cyclooxygenase-2 (COX-2) and epidermal growth factor receptor (EGFR) has been detected in many types of cancer. Although COX-2 and EGFR are closely related to each other, the exact mechanism of COX-2 in tumors has not been well understood. In this study, we investigated the relationship between COX-2 and EGFR in cancer cells. Using two cell lines stably overexpressing COX-2 (HCT-116-COX-2 and H460-COX-2) and a stable line of COX-2 knockdown MOR-P cells, we analyzed patterns of COX-2 and EGFR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…39 The effect of COX-2-dependent PGs on these signaling pathways have been recently studied using cell lines stably overexpressing COX-2. 40 Our data in COX-2 Tg hepatocyte-like cells verify moderate activation of JNK, Erk, and p38 in CHL-C cells.…”
Section: Cox-2 In Chemical Hepatocarcinogenesis 1371supporting
confidence: 67%
“…39 The effect of COX-2-dependent PGs on these signaling pathways have been recently studied using cell lines stably overexpressing COX-2. 40 Our data in COX-2 Tg hepatocyte-like cells verify moderate activation of JNK, Erk, and p38 in CHL-C cells.…”
Section: Cox-2 In Chemical Hepatocarcinogenesis 1371supporting
confidence: 67%
“…4F). In addition to its potential role in tumor promotion and progression, overexpression of COX-2 has been suggested to promote resistance to EGFR TKIs in both EGFR-dependent and EGFR-independent manners (Krysan et al, 2005;Kim et al, 2009), and addition of specific COX-2 inhibitors can synergize the effect of EGFR TKIs in some preclinical studies Zhang et al, 2005;Buchanan et al, 2007). The induction of COX-2 transcription by EGFR is well documented and mostly relies on EGFR tyrosine kinase activity (Rogers et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that COX-2 overexpressing cancer cells are more resistant to doxorubicin and gefitinib (46, 47). Moreover, STAT1 has been shown to play a role in chemo- and radio-resistance.…”
Section: Discussionmentioning
confidence: 99%